Analysis of Differences in Methods and Techniques for Translation of Surah Al-Insyirah in Translation by the Indonesian Ministry of Religion and Buya Hamka - Muh. Muhram; Andi Abdul Hamzah (Values: Jurnal Kajian Islam Multidisiplin, 2025)
This research examines the differences in translation methods and techniques applied in translating Surah Al-Insyirah by the Ministry of Religion of the Republic of Indonesia (Kemenag RI) and Buya Hamka. Translation of the Quran is a complex activity because it involves linguistic, religious elements, as well as cultural and interpretive contexts. Using a qualitative descriptive approach and comparative analysis, this research compares the results of translations of eight verses in Surah Al-Insyirah from both sources. The results of the analysis show that the Indonesian Ministry of Religion mostly uses a literal approach with techniques such as general equivalents and exploitation. On the other hand, Buya Hamka tends to use a free (dynamic) translation approach through modulation, adaptation and amplification techniques to clarify meaning in the Indonesian context. These differences reflect the ideological approach and institutional background of each translator in conveying the message of the Koran. These findings emphasize the importance of choosing appropriate translation methods and techniques so that the meaning of sacred texts can be conveyed effectively to the reader.